Transcriptomic analysis of flower induction for long-day pitaya by supplementary lighting in short-day winter season - Rui Xiong (BMC Genomics, 2020)
Abstract Background Pitayas are currently attracting considerable interest as a tropical fruit with numerous health benefits. However, as a long-day plant, pitaya plants cannot flower in the winter season from November to April in Hainan, China. To harvest pitayas with high economic value in the winter season, it is necessary to provide supplementary lighting at night to induce flowering. To further explore the molecular regulating mechanisms of flower induction in pitaya plants exposed to supplementary lighting, we used de novo RNA sequencing-based transcriptomic analysis for four stages of pitaya plants subjected to light induction. Results We assembled 68,113 unigenes in total, comprising 29,782 unigenes with functional annotations in the NR database, 20,716 annotations in SwissProt, 18,088 annotations in KOG, and 11,059 annotations in KEGG. Comparisons between different samples revealed different numbers of significantly differentially expressed genes (DEGs). A number of DEGs involved in energy metabolism-related processes and plant hormone signaling were detected. Moreover, we identified many CONSTANS-LIKE, FLOWERING LOCUS T, and other DEGs involved in the direct regulation of flowering including CDF and TCP, which function as typical transcription factor genes in the flowering process. At the transcriptomic level, we verified 13 DEGs with different functions in the time-course response to light-induced flowering by quantitative reverse-transcription PCR analysis. Conclusions The identified DEGs may include some key genes controlling the pitaya floral-induction network, the flower induction and development is very complicated, and it involves photoperiod perception and different phytohormone signaling. These findings will increase our understanding to the molecular mechanism of floral regulation of long-day pitaya plants in short-day winter season induced by supplementary lighting.